Climate smart agriculture (CSA) - Verhagen, J; Vellinga, Theun V.; Neijenhuis, F; Jarvis, Tu; Jackson, L.; Caron, P.; Torquebiau, Emmanuel F.; Lipper, Leslie; Fernandes, E; Entsua-Mensah, R.E.M.; Vermeulen, Sonja J. (2014)
Climate change fundamentally shifts the agricultural development agenda. Changing temperature and precipitation, sea level rise, and the rising frequency of extreme climate events will signiﬁcantly reduce global food production in this century unless action is taken. Major investments, private and public, will be needed.! Adapting agriculture to climate change is necessary to achieve food security, and agricultural mitigation can also reduce atmospheric greenhouse gas concentrations and slow climate change itself. There are many drivers of change aﬀecting agricultural sectors around the world, including population growth, changes in consumer demand and market integration. Climate Smart Agriculture is an integrated approach to achieve food security in the face of climate change, while also mitigating climate change and contribute to other development goals.